SLA major theoretical views: putting the jigsaw pieces together - Sugeng Hariyanto (UPT P2M Politeknik Negeri Malang, 2011)
Second language acquisition is a complex internal process. There no guarantee that what it is known now is the complete picture. In other words, there may be some other aspects that have not been revealed. This article tries to briefly review the major theories in Second Language Acquisition (SLA). Behaviorists sees human language is acquired and maintained via stimulus‐response‐reinforcement sequence. Innatist theory first of all states that conditioning model is not appropriate to explain how human language is acquired based on the fact that children can produce novel sentences in new combination that has never been heard. Interactinists point out that LAD/UG or innate capacity alone does not help much. Finally, cognitivist view sees that in acquiring a language, a human being needs a mental capacity. All theoretical views will not argue the claim that human being needs mental capacity to acquire language. This article ends in its effort to put “the jigsaw pieces” from the schools of SLA theory to form a picture of how second language is theoretically acquired.